ASSESSMENT OF KNOWLEDGE, ATTITUDE AND PERCEPTION OF HUMAN PAPILLOMA VIRUS VACCINATION AMONG PARENTS OF YOUNG GIRLS (AGED 8 – 12) IN MBARARA CITY. A CROSS-SECTIONAL STUDY. - Twikirize, Bright; Kalibwani, Rebecca; Amanyire, Jordan (Student’s Journal of Health Research Africa, 2023)
Introduction: To reduce the cervical cancer burden, many governments have emphasized the Human papillomavirus (HPV) vaccine as an important prevention strategy. Despite its effectiveness in preventing human papillomavirus (HPV) infection and free HPV immunization programs, vaccine acceptance is not guaranteed as some cultures are still against it due to various reasons. This study was conducted to assess the knowledge, attitude, and perception of human papillomavirus vaccination (HPV) among parents of young girls (aged 8 – 12) in Mbarara City. Methodology: The study was cross-sectional employing both qualitative and quantitative approaches for data collection and analysis. Information was collected from a sample of 288 respondents and 12 key informants using questionnaires and interviews. Data was analyzed using Microsoft Excel and STATA Version 18.0 Results: The study discovered that the level of Knowledge on HPV vaccination among parents of young girls was relatively low (41.3%) despite most respondents revealing to have heard about HPV and its associated infections like cervical cancer and genital warts. The study also found out that a large portion of community members (62.1%) still had negative attitudes towards the vaccine which has negatively affected their perceptions. Negative attitudes and perceptions equally played a big role towards vaccination leading to low vaccine acceptability in the area. The study further discovered a wide knowledge gap about HPV infection and HPV vaccine uptake (42%) and this has to be addressed. Conclusion: In conclusion, the study confirmed that knowledge about human papillomavirus vaccination (HPV) was low and attitude and perception of human papillomavirus vaccination (HPV) was poor among parents of young girls (aged 8 – 12). Recommendations: Tailored community-based interventions and sensitization programs are a viable means to achieve this for multiple reasons. There is a need for specific training for healthcare workers who are the first contact point for patients.